Delayed bowel perforation in electrocution: An unpredictable foe. (December 2020) - Goyal, Divakar; Dhiman, Ajay; Jagne, Nilesh; Rattan, Amulya
Abstract: Electrocution injuries, particularly high voltage, are uncommon, but can be devastating. Thermal burns, arrhythmias and myonecrosis are commonly known and monitored complications of electrical injuries. Direct thermal trauma to internal viscera is also known and almost all internal organs have been reported to be affected, bowel being the most common. However, bowel perforation occurring in a delayed fashion is one rare, dreaded and erratic complication of electrocution, making it a dangerous pitfall if missed. Alimentary tract perforations can present on a delayed basis in high voltage electrocution injuries; advise for clinical follow up must incorporate this possibility at the time of discharge. Presentation of delayed visceral injuries is subtle & atypical, and post burn immunosuppression may play a part for such presentation. We suggest that all victims of high voltage electrocution with abdominal wall burns receive diagnostic laparoscopy and/or CECT abdomen as part of workup of their injuries. Any non-enhancing segment of bowel on CECT, howsoever small, should be prudently evaluated with laparoscopy. Highlights: Bowe perforations can present in a delayed fashion in high voltage electric injuries (HVEI). Awareness of this rare entity is paramount for surgeons treating electrical injuries. Presentation of post-electrocution visceral injuries can be subtle, atypical and therefore prone to delayed diagnosis leading to increased morbidity and mortality. All victims of HVIE with abdominal wall burns should undergo diagnostic laparoscopy and/ or CECT abdomen.